Semantic Prosody of Research Verbs: A Corpus-Informed Study - Ghuzayyil Mohammed Al-Otaibi (National Research University Higher School of Economics, 2022)
Background: Synonymous words behave differently, and language users should be aware of the fact that though near-synonyms share similar denotational meanings, they require different collocates. Further, with specific collocates, they provoke a special affective meaning called semantic prosody. To give an example of this problematic area, researchers use a lot of reporting verbs that merely describe an opinion such as argue, claim, believe, etc. or state facts such as find, confirm, cite, etc. Such verbs cannot be used interchangeably as some novice researchers usually do when they discuss their findings or compare their results with others'. Purpose: This study aimed at examining the semantic prosody of 24 research verbs commonly used by researchers. For this purpose, collocational behavior of nearly synonymous verbs was examined. Compared to previous studies, this study considered only adverbs co-occurring with such research verbs. Methods: The researcher used the Directory Open Access Journals (DOAJ), which is of 2.6 billion words and 659,132 texts, and focused on predicational adverbs that end in -ly. For the purpose of the study, adverbs with positive semantic prosody are those proving a stronger attitude towards the proposition, improving the quality, quantity, manner of a piece of information or its the relation to the topic or those suggesting a higher level of certainty. Results: Investigating 24 research verbs related to hypothesizing, reporting, and summarizing, the researcher found that such verbs have different sets of collocates and thus distinct semantic prosodies. Results showed that 12 of the research verbs were positive (i.e., quantify, argue, claim, suggest, state, mention, indicate, outline, summarize, encapsulate, recapitulate, and reveal), whereas 12 verbs (i.e., hypothesize, review, conclude, presume, posit, assume, theorize, speculate, note, report, find, and postulate) were neutral. Implications: The study has its own implications for writing instructors and researchers. Novice researchers should not use some research verbs interchangeably as they require different collocates of adverbs. Further, future research should address the relationship between word's etymology and semantic prosody as the present study showed that verbs derived from Latin (e.g., conclude, hypothesize, postulate, etc.) are neutral compared to those that are originally French.